Strategy For Developing Medical Record Service Capabilities For Health Human Resources At Pertamina Pangkalan Brandan Hospital In 2023 - Febria Dian Ekayani; Crismis Novalinda Ginting; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2024)
Human resource development is basically a strategy to improve the performance of health workers which reflects the ability of organizational members to work, meaning that the performance of each health worker is assessed and measured according to criteria determined by the hospital organization. This research aims to analyze development of medical record service capabilities for Health Human Resources. This type of research is quantitative using a cross-sectional study.This research conducted inPertamina Pangkalan Brandan Hospitalon the monthSeptember 2022 to Mayin 2023.The sample in this study was all health workers who worked at Pertamina Pangkalan Brandan Hospital,namely as many as 140 people. Data analysis was carried out using univariate and bivariate analysis. Based on the research results, it is known that there is an impact on the development of human resources using the on-the-job training method in the field of Medical Records services, there is an impact on the development of human resources using the demonstrator and example training method in the field of Medical Records services, there is an impact on the development of human resources using the Apprenticeship training method in the field of Medical Records services in Pertamina Pangkalan Brandan Hospital in 2023. Based on the conclusions, it is hoped that the Training Team, which is likened to activating and managing human resources in Pertamina Pangkalan Brandan Hospital, should always be able to evaluate the training needs of its employees. The training required by each nurse, such as new nurses, staff who have worked for a long time, will of course be different.